The Isolation, Identification and Characterization of a Wild-Type Strain Pseudomonas aeruginosa PM1012 from the Cloacal Microbiota of a Common Wall Lizard (Podarcis muralis Laurenti, 1768) - Irina Lazarkevich; Stephan Engibarov; Simona Mitova; Rumyana Eneva; Tsvetelina Paunova-Krasteva; Dayana Borisova; Emiliya Vacheva; Nikola Stanchev; Steliyana Popova; Yana Gocheva; Maria Gerginova (Applied Microbiology)
Pseudomonas aeruginosa is a ubiquitous environmental Gram-negative bacterium and also an opportunistic pathogen for both humans and animals, causing acute or chronic infections. It has been frequently detected in healthy and diseased reptiles, more commonly in captive ones. Since most studies are primarily on clinical isolates, the pathogenic potential of strains originating from wild animals is poorly explored. We isolated the strain P. aeruginosa PM1012 from the cloacal microbiota of a common wall lizard (Podarcis muralis Laurenti, 1768) from a free-living population. The effect of temperature, pH and salinity on its growth was evaluated. Antibiotic resistance, the expression of several virulence factors as some extracellular enzymes, pyocyanin production and biofilm formation were also assessed. Apart from intrinsic resistance, the newly isolated strain P. aeruginosa PM1012 presented an antibiotic susceptibility profile with a low resistance rate limited to meropenem and intermediate to ceftazidime and aztreonam. Protease, lipase and gelatinase secretion was detected. Strong pyocyanin production was observed in the optimal range of growth conditions. An excellent biofilm-forming capacity was manifested.